Clinical characteristics of firearm-related injuries in children in Turkey - Vatansever, Göksel; Battal, Fatih; Özkaya, Pınar Yazıcı; Yener, Nazik; Yıldızdaş, Dinçer; Duran, Rıdvan; Tekin, Deniz; Ulukol, Betül; Kendirli, Tanıl; Güleryüz, Okşan Derinöz; Arslanköylü, Ali Ertuğ; Havan, Merve; et al. (The Turkish Journal of Pediatrics, 2022)
Background. A significant number of children are injured by or die from firearm-related incidents every year, although there is a lack of global data on the number of children admitted to pediatric emergency departments (PEDs) and pediatric intensive care units (PICU) with firearm injuries. This study is the most comprehensive analysis of firearm injuries sustained by children in Turkey to date. Methods. This multicenter, retrospective, cohort study was conducted between 2010 and 2020 with the contributions of the PEDs, PICUs, intensive care units, and surgery departments of university hospitals and research hospitals. Results. A total of 508 children were admitted to hospital with firearm-related injuries in the research period, although the medical records of only 489 could be obtained. Of the total admissions to hospitals, 55.0% were identified as unintentional, 8.2% as homicide, 4.5% as self-harm, and 32.3% as undetermined. The Glasgow Coma Scale (GCS) and ventilation support were found to be the most significant predictors of mortality, while head/neck injury, length of stay (LOS) in the hospital and surgical interventions were found to be the most significant predictors of disability. The overall mortality of firearm-related injuries was 6.3%, and the mortality for children admitted to the PICU was 19.8%. The probability of disability was calculated as 96.0% for children hospitalized with firearm injuries for longer than 75 days. Conclusions. Head/neck injury, LOS in the hospital, and surgical interventions were found to be the most significant parameters for the prediction of disability. Hospitalization exceeding 6 days was found to be related to disability.